Financial Development and Geographic Isolation: Global Evidence - Oasis Kodila-Tedika; Simplice Asongu; Matthias Cinyabuguma (African Governance and Development Institute (AGDI), 2016)
Using cross-country differences in the degree of isolation before the advent of technologies in sea and air transportation, we assess the relationship between geographic isolation and financial development across the globe. We find that pre-historic geographical isolation has been beneficial to development because it has contributed to contemporary cross-country differences in financial development. The relationship is robust to alternative samples, different estimation techniques, outliers and varying conditioning information sets.
Keywords: F15; G15; N7; O16; O50; 330; Financial development; Isolation; Agglomeration; Globalization